The Gospel of John ; v. 1 a commentary - Keener, Craig S. 1960- (Peabody, MA Hendrickson, 2003)
Contents : v. 1 : Table of contents, Introduction, Chapter 1:1 - 10:42.
Bibliographical references and indexes are included in v. 2.
Keywords: Bible. N.T. John -- commentaries